Spatiotemporal dynamics of vegetation in response to climate variability in the Borana rangelands of southern Ethiopia - Worku, Mitiku Adisu; Feyisa, Gudina Legese; Beketie, Kassahun Ture; Garbolino, Emmanuel (Frontiers in Earth Science, 2023)
In this paper, we analysed the spatiotemporal dynamics of vegetation and its association with climate variables in the Borana rangelands of southern Ethiopia. Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Difference Vegetation Index (NDVI) data namely MODIS/TERRA, MOD09Q1 16-day L3 Global 250 m version 6 from National Aeronautics &Space Agency (NASA) United States Geological Survey (USGS) and climate data from 2000 to 2018 were obtained from the National Meteorological Agency (NMA) of Ethiopia were used to determine the vegetation dynamics at both annual and seasonal timescales. The results indicated that NDVI varies between 0.31 and 0.41 and the study area is dominated by sparse vegetation mainly shrubs and grasslands. NDVI revealed poorer vegetation growth than vegetation condition index (VCI) between 2000 and 2018 although variations were observed spatiotemporally. Rainfall was highly variable at both annual and seasonal scales than the temperature during the studied years. The climate variables significantly determined the condition of vegetation particularly during the growing seasons than in other periods. A significant strong positive correlation was observed between NDVI, VCI and climate variables during the primary (Belg) and short (Meher) rainy seasons in Borana rangelands. The results of this study are beneficial for the development of proper policies of intervention and provide information for sustainable rangeland management.